SIMULASI KINERJA JARINGAN GSM KETIKA HANDOVER MENGGUNAKAN NETWORK SIMULATOR (NS2) - muchamad wahyudin; helmy Fitriawan; - - herlinawati (Universitas Lampung, 2013)
There is a process called handover in GSM network. Handover is the displacement of the mobile station from one base transceiver station (BTS) to another BTS. With handover, the mobile station can change position anytime during the talks and conversations handling the transfer of one BTS to another BTS when customers move from one cell to another.The study was conducted using a software network simulator version 2 (NS-2) with a linux operating sitem 10.10. This study discusses the performance of the current GSM intra Base Station Controller (BSC) handover and inter BSC to measure the parameters of Quality of service (QOS). This study applied some variables from the packet size and speed.From the simulation results, the value of the Throughput average and packet loss occurs at the optimum speed of 17 m / s at the intra-and inter BSC. On delay average, there is the fluctuating value of intra and inter BSC